INSTITUTIONAL AND FINANCIAL MECHANISMS FOR IMPROVING THE EFFICIENCY OF PROJECT FINANCING OF INVESTMENT PROJECTS IN COMMERCIAL BANKS - Abdurazakova, Nasiba Sultanovna (THE INNOVATION ECONOMY, 2026)
This article examines institutional and financial mechanisms for improving the efficiency of project financing of investment projects in commercial banks. The study is based on a theoretical analysis of project financing principles, including cash flow–based lending, risk allocation, and institutional conditions influencing the effectiveness of project-based financing. Particular attention is given to identifying institutional and methodological limitations that constrain the practical application of project financing in commercial banks. Based on the analysis, the article proposes an integrated institutional and financial mechanism aimed at enhancing the efficiency of project financing. The proposed mechanism emphasizes the strengthening of regulatory and legal frameworks, the establishment of specialized project finance units within commercial banks, the improvement of project-specific risk management practices, and the expansion of access to long-term funding sources. The findings of the study contribute to the development of project financing theory and provide practical recommendations for commercial banks and policymakers seeking to support investment-driven economic growth, particularly in transition economies.